The putative role of gut microbiota in cancer: Cysteine is a pivotal coin - Serpa, Jacinta (Frontiers in Gastroenterology, 2022)
Tumor metabolism is mandatory for the proper adaptation of malignant cells to the microenvironment and for the acquisition of crucial cellular skills supporting the systemic spread of cancer. Throughout this journey, the contribution of the gut microbiota to the bioavailability of nutrients supporting the bioenergetic and biosynthetic requirements of malignant cells is an issue. This review will focus on the role of cysteine as a coin that mediates the metabolic crosstalk between microbiota and cancer. The key points enclose the way cysteine can be made available by the microbiota, by degradation of more complex compounds or by de novo synthesis, in order to contribute to the enrichment of the colonic microenvironment as well as to the increase of cysteine systemic bioavailability. In addition, the main metabolic pathways in cancer that rely on cysteine as a source of energy and biomass will be pointed out and how the interspecific relationship with the microbiota and its dynamics related to aging may be relevant points to explore, contributing for a better understanding of cancer biology.